"The Year of China in South Africa": Two Scenes from Johannesburg. - Mingwei Huang (Radical History Review, 2018)
The article reflects on two incidents from Johannesburg, South Africa that declared 2015 as "The Year of China in South Africa." It mentions that Bank of China advertisements covered multiple walls and conjured the largesse of Chinese investment and infrastructure in Africa during the sixth Forum on China-Africa Cooperation meeting in Johannesburg. It informs about employment for Zimbabwean and Malawian economic migrants in Johannesburg's China Malls.